Poverty, pro-poor growth and mobility - Yin Zhang; Guanghua Wan (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2006)
This paper proposes a framework for incorporating longitudinal distributional changes into poverty decomposition. It is shown that changes in the Sen-Shorrocks-Thon index over time can be decomposed into two components—one component reflects the progressivity of income growth among the original poor, the other measures the extent of downward mobility experienced by the incumbent poor. The decomposition is applied to appraising poverty trends in China between 1988 and 1996. The results indicate that the proposed decomposition can complement the widely-used growth-distribution decomposition in providing insights into poverty dynamics.
Keywords: O10; O53; D31; 330; poverty decomposition; Sen index; longitudinal data; China; Armut; Disparitätsmaß; China